PRESUPPOSITIONS: THE HIDDEN FORCE SHAPING EVERYDAY CONVERSATIONS - Eragamreddy, Nagamurali (Premise: Journal of English Education and Applied Linguistics, 2024)
The present investigation explores the key questions: presuppositions exist in conversation, interact with speech patterns, and function with other language elements in real-world communication beyond the speaker's intended meaning. According to linguistic theory, presuppositions significantly strengthen communication through implicit meanings that work collaboratively with linguistic structures to promote understanding, establish relationships, and elicit associated cultural convictions (Allan, 2014). Data was collected using a mixed-method methodology from various sources, including conversations, interviews, speeches given in public, articles, and literary excerpts. Discourse and pragmatic analysis were deployed to explore how presuppositions interact with speech patterns, conversational dynamics, and contextual comprehension. The results show that presuppositions often influence communication by embedding hidden meanings into questions, metaphors, and negations. Although these presuppositions improve discourse meaning-making, unspoken presuppositions might lead to misunderstandings. It was discovered that presuppositions played a significant role in establishing connections between individuals, establishing emotional bonds, and gently directing interpretations in cross-cultural settings. According to the study's findings, presuppositions are essential to everyday discourse and have significant implications for pragmatic competence, intercultural communication, and language enhancement.